2021
DOI: 10.1177/21676968211005598
|View full text |Cite
|
Sign up to set email alerts
|

The Associations Between Internalized Racism, Racial Identity, and Psychological Distress

Abstract: Internalized racism, or the acceptance of negative stereotypes about one’s own racial group, is associated with psychological distress; yet, few studies have explored the longitudinal impact of internalized racism on the psychological well-being of African American emerging adults. Furthermore, racial identity’s role as a protective factor in the context of internalized racism remains unclear. This study examined the longitudinal impact of internalized racism on psychological distress (depressive and anxiety s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
12
1
6

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 33 publications
(20 citation statements)
references
References 48 publications
1
12
1
6
Order By: Relevance
“…Racism has the ability to affect health via physical, psychological, social, functional, and spiritual domains. Specifically, racism-related stress has been related to hypertension ( Williams and Neighbors, 2001 , Anderson, 1989 ), cardiovascular issues ( Paradies et al, 2015 Sep 23 ), depression ( Willis et al, 2021 Aug 1 ), psychological distress ( Jackson et al, 1996 , Kelly et al, 2020 Apr ), and health behaviors such as eating disorders ( Glass et al, 2020 Nov ), substance abuse ( Jones et al, 2019 Jun , Desalu et al, 2019 Jun , Frazer et al, 2018 Feb ) and violence ( Sutton et al, 2020 Feb , Johnson et al, 2021 ). Additionally, racism-related stress has effects on social (ability to trust and interact with others) ( Hicken et al, 2013 Jun 1 , Odoms-Young, 2018 ), functional (academic and financial achievement) ( Grace and Nelson, 2019 Oct 2 , Butler-Barnes et al, 2018 Oct ) and spiritual (faith in higher powers) well-being ( Drolet and Lucas, 2020 Dec , Bailey et al, 2020 ).…”
Section: Minority Stress Theorymentioning
confidence: 99%
See 1 more Smart Citation
“…Racism has the ability to affect health via physical, psychological, social, functional, and spiritual domains. Specifically, racism-related stress has been related to hypertension ( Williams and Neighbors, 2001 , Anderson, 1989 ), cardiovascular issues ( Paradies et al, 2015 Sep 23 ), depression ( Willis et al, 2021 Aug 1 ), psychological distress ( Jackson et al, 1996 , Kelly et al, 2020 Apr ), and health behaviors such as eating disorders ( Glass et al, 2020 Nov ), substance abuse ( Jones et al, 2019 Jun , Desalu et al, 2019 Jun , Frazer et al, 2018 Feb ) and violence ( Sutton et al, 2020 Feb , Johnson et al, 2021 ). Additionally, racism-related stress has effects on social (ability to trust and interact with others) ( Hicken et al, 2013 Jun 1 , Odoms-Young, 2018 ), functional (academic and financial achievement) ( Grace and Nelson, 2019 Oct 2 , Butler-Barnes et al, 2018 Oct ) and spiritual (faith in higher powers) well-being ( Drolet and Lucas, 2020 Dec , Bailey et al, 2020 ).…”
Section: Minority Stress Theorymentioning
confidence: 99%
“…In turn, these social threat-related structural and connectivity changes in the salience network - in addition to HPA-axis dysregulation - can lead to hypervigilance, which can result in increased vulnerability to subsequent social threats ( Tull et al, 2005 Feb ). These processes contribute to a variety of deleterious physical and mental health consequences such as anxiety and depression disorders ( Willis et al, 2021 Aug 1 , Misiak et al, 2014 Sep ), schizophrenia ( Edwards, 2008 Jun 25 ), chronic pain ( Burgess et al, 2009 Nov 1 , Wagner et al, 2015 Aug ), high blood pressure, cardiovascular disease, diabetes and obesity among others ( Goosby et al, 2018 Jul , Herman and Panksepp, 1978 Aug 1 ).…”
Section: Minority Stress Theorymentioning
confidence: 99%
“…Regard refers to how an individual feels, either positively or negatively about African American group membership in both a private and public view (Sellers, 1998). Regard can also be connected to internalized racism, allowing members of a racial group to have negative attitudes towards their own racial group due to social norms or experiences among individuals that share their same racial identity (Willis, 2021). This experience was discussed in the interviews and supported the results reported by the students.…”
Section: Construct 3: Dominant/white Culture and Practices Within The...mentioning
confidence: 52%
“… 23 , 24 Associations between internalized racism (i.e., the acceptance of negative stereotypes by the stigmatized group about their own race) 25 and anxiety, depressive symptoms, and psychological distress, all of which contribute to overall worse health outcomes, have been well documented. 23 , 24 , 26 , 27 …”
Section: Discussionmentioning
confidence: 99%
“…23,24 Associations between internalized racism (i.e., the acceptance of negative stereotypes by the stigmatized group about their own race) 25 and anxiety, depressive symptoms, and psychological distress, all of which contribute to overall worse health outcomes, have been well documented. 23,24,26,27 Most participants in this study were unaware that race has been used as a modifying factor in clinical equations such as the calculation of kidney or lung function and stated that race should not be included in these equations. Several studies have shown that racially discriminatory algorithms can exacerbate existing health inequities.…”
Section: Discussionmentioning
confidence: 99%